A genotype–phenotype correlation in split-hand/foot malformation type 1: further refinement of the phenotypic subregions within the 7q21.3 locus - Sowińska-Seidler, Anna; Socha, Magdalena; Szoszkiewicz, Anna; Materna-Kiryluk, Anna; Jamsheer, Aleksander (Frontiers in Molecular Biosciences, 2023)
Background: Split hand/foot malformation type 1 (SHFM1) refers to the group of rare congenital limb disorders defined by the absence or hypoplasia of the central rays of the autopods with or without accompanying anomalies, that is, hearing loss, craniofacial malformation and ectodermal dysplasia. Consequently, the condition is characterized by clinical variability that hinders diagnostic and counselling procedures. SHFM1 is caused by pathogenic variants affecting the DLX5/6 genes and/or their tissue-specific enhancers at the 7q21.3 locus. Herein, we report on seven patients from five unrelated Polish families affected by variable symptoms of the SHFM1 spectrum, all harbouring 7q21.2-q21.3 rearrangements and provide a genotype-phenotype correlation in the studied cohort. Methods: We applied GTG banding, array-based comparative genomic hybridization (aCGH) and whole genome sequencing (WGS) in order to identify the causative aberrations in all affected patients. Results: The identified pathogenic structural variants included deletions at 7q21.2-q21.3 and translocations involving the 7q21.3 locus, i.e. t(7;10)(q21.3;q22.2) and t(7;12)(q21.3;q21.23) in all affected individuals. Interestingly, a sporadic carrier of the latter aberration, presented with SHFM1 phenotype with additional features overlapping with the Baker-Gordon syndrome (BAGOS), which resulted from the translocation breakpoint at chromosome 12 within the SYT1 gene. Conclusions: Clinical variability of the studied cohort reflects the composition of the DLX5/6 regulatory elements that were dislocated from their target genes by chromosomal rearrangements. The correlation of our data with the previously published observations, enabled us to update the phenotypic subregions and regulatory units within the SHFM1 locus. In addition, we present the first case of SHFM1 and BAGOS-like phenotype that resulted from translocation breakpoints at chromosomes 7 and 12, both of which were pathogenic, and consequently, we show the first evidence that BAGOS can also result from the regulatory loss-of-function SYT1 mutations. With this paper, we emphasize the utility of sequence-based approaches in molecular diagnostics of disorders caused by regulatory structural variants.